A second new species of Tyrrhenoleuctra discovered by means of molecular data: Tyrrhenoleuctra lusohispanica n. sp. (Plecoptera: Leuctridae) - de Figueroa, José Manuel Tierno; Fochetti, Romolo (Zootaxa, 2014)
Tyrrhenoleuctra lusohispanica sp. n., a new species of the leuctrid genus Tyrrhenoleuctra from the southern Iberian Peninsula (southern Portugal and Spain) is described solely on molecular characters. Molecular analyses clearly indicated the distinctness of this species and demonstrated the presence of cryptic species in the genus Tyrrhenoleuctra. We also describe the systematic affinities of T. lusohispanica sp. n. to other species in the genus. With all Tyrrhenoleuctra species, T. lusohispanica sp. n. exhibits marked phenotypic variability.